Mental Health and Family Functioning in Patients and Their Family Members after Traumatic Brain Injury: A Cross-Sectional Study - Mari S. Rasmussen; Juan Carlos Arango-Lasprilla; Nada Andelic; Tonje H. Nordenmark; Helene L. Soberg (Brain Sciences, 2020)
Traumatic brain injury (TBI) affects the family as a whole. This study aimed to describe and compare mental health and family functioning in TBI patients and their family members, and to identify individual and family-related factors that were associated with mental health. It was conducted at an urban, specialized, TBI outpatient clinic and included 61 patients with mild to severe TBI and 63 family members. Baseline demographics and injury-related data were collected, and the participants answered standardized, self-reported questionnaires 6–18 months post-injury that assessed mental health; general health; family functioning, communication, and satisfaction; depression and anxiety; self-efficacy; resilience; and condition-specific quality of life. The patients reported significantly worse mental health, depression, resilience, self-efficacy, and general health compared with the family members. Patients and family members had similar perceptions, showing balanced family functioning, high family communication levels, and moderate family satisfaction. Factors significantly associated with mental health in patients and family members were depression, anxiety, and resilience, explaining 56% of the variance (p < 0.001). Family-related factors were not associated with mental health. The disease burden was mainly on the patients; however, the family members also reported emotional distress. Family-targeted interventions across the TBI continuum should be considered.